Uso de hialuronidato de sódio para tratamento de deslocamento anterior de disco articular com travamento bucal - Lyrio, Mariana Camilo Negreiros (2010)
Temporomandibular joint disorders causing limitation of mouth opening and pain may be related to the restriction of slipping or forward displacement of the mandibular condyle. Temporomandibluar arthrocentesis is the lavage of the joint and is regarded as a simple method that produces good results in patients with these symptoms. This article reports a case of disc displacement and closed lock in a patient who reported limited mouth opening and pain as the main symptoms. The treatment proposed was arthrocentesis and lavage, combining a corticosteroid with a sodium hyaluronate solution. It is concluded that arthrocentesis is a simple, efficient and barely invasive method for particular types of temporomandibular joint disorders and should be considered before opting for more invasive surgical procedures.